Global value chain approach and micro-level analysis: a innovative framework of analytical elements and future research opportunities - Ribeiro, Vinícius Souza (2024)
Objective: This article proposes an innovative framework of elements for quantitative and micro-analytical investigations in the field of the Global Value Chain (GVC) approach. It also seeks to suggest some mutual benefits from bridging this approach with the Structure-Conduct-Performance (SCP) model. Methodology: A literature review and bibliometric analysis were conducted on studies associated with the GVC and SCP approaches, using the Scopus and Google Scholar databases. Originality/Relevance: In the literature related to the GVC approach, researchers recognize a gap in quantitative and micro-analytical studies. This research contributes to filling that gap. Moreover, it proposes a connection between the GVC and SCP approaches. Main Results: It identifies the obstacles to the development of quantitative and/or micro-level research in the field of GVC and presents a framework of analytical elements. Theoretical/Methodological Contributions: It discusses the limitations and capabilities of using these elements and the potential impacts of future research aimed at addressing gaps in the GVC field. Additionally, it summarizes some benefits of bringing the GVC and SCP paradigms closer together. Social/Management Contributions: It highlights the mutual benefits of linking both approaches and underscores the importance of this for the greater consolidation and acceptance of GVC analysis in academic and political environments. Finally, it emphasizes the academic and political relevance of the studies it seeks to promote.